Employee regret and disappointment: Creation of a scale and foundational application of the approach/avoidance framework. Issue 2 (3rd January 2022) - Howard, Matt C.; Smith, Mickey B.
Abstract: A growing number of calls have been made for a discrete‐emotions approach in organisational research, and we answer these calls by theoretically and empirically distinguishing the effects of regret and disappointment by applying the approach/avoidance framework. We predict that regret positively relates to avoidance motivation, whereas disappointment both positively relates to avoidance motivation and negatively relates to approach motivation. We also predict that approach and avoidance motivations mediate the effects of regret and disappointment on employee outcomes, including job satisfaction, organisational citizenship behaviors, voice, counterproductive work behaviors, withdrawal, and turnover intentions. To test these predictions, we conduct five studies to develop theoretically driven and psychometrically sound scales to measure both emotions—the Employee Regret and Disappointment Scales (ERDS). The results of two final studies support the distinct effects of regret and disappointment on important employee outcomes and the mediating effects of approach/avoidance motivations in these relations. We close by discussing the theoretical and practical implications with suggestions for future research.